Correlation of Insulin Resistance with Thyroid Profile in Streptozotocin Induced Type 2 Diabetic Rats - Sidra Arshad; Muhammad Mazhar Hussain (Journal of Rawalpindi Medical College, 2013)
Background: To assess the association between insulin resistance, thyroid profile and glucose levels in type 2 diabetes mellitus. Methods: In this randomized control trial, 60 Sprague Dawley rats were divided into control and diabetic groups. All the rats were checked for euglycemia and euthyroidism at the beginning of the study by analyzing plasma glucose and serum thyroid stimulating hormone (TSH) levels. The diabetic group was fed high fat diet while control group was given normal pellet diet. After 2 weeks diabetic rats were intraperitoneally administered low dose of streptozotocin and saline to the control group. Development of type 2 diabetes was confirmed by checking homeostatic model for insulin resistance (HOMA-IR) and plasma glucose levels. Specific diet for the two groups was continued for another five weeks. Terminal blood samples were analyzed for plasma glucose, serum insulin, T3, T4 and TSH levels. Results: Plasma glucose and serum insulin levels were found significantly elevated (p-0.001) in the diabetic group. HOMA-IR was increased in the diabetic group (p=0.001). Serum T4 and TSH levels were significantly elevated (p=0.001) while no significant change in serum T3 was noticed in the diabetic group. Pearson correlation coefficient revealed positive correlation between insulin resistance and T4 level (r=0.36) in the diabetic group. Positive correlation was found in the diabetic group between glucose level and T3 (r=0.36) and plasma glucose and T4 (r=0.35). Conclusion: Development of thyroid dysfunction and insulin resistance interplay in development of hyperglycemia in type 2 diabetes mellitus.